Hubungan Pengetahuan dan Motivasi dengan Kepatuhan Minum Obat Anti Tuberkulosis (Oat) pada Pasien TB - Yanti, I Gusti Ayu Komang Lia Purnama; Widyandari, Ni Made Ayu Sukma; Diwyami, Ni Putu (ProHealth Journal, 2025)
TB patients' knowledge and motivation will have an impact on their compliance in implementing the treatment program. The better a person's knowledge, the more obedient they will be in carrying out quality treatment and the higher a person's motivation, the higher a person's enthusiasm will be to achieve healing. The aim of this research is to determine and describe the relationship between knowledge and motivation and adherence to taking anti-tuberculosis medication. The type of research used is cross-sectional. The population in this study was 136 patients with tuberculosis in the work area of ​​South Denpasar Health Center II with a sample size of 114. The measuring tool used was a questionnaire. Data analysis used univariate and bivariate analysis with the chi-square test. The results show that knowledge and adherence to taking medication shows there is a relationship (p value 0. 089), motivation and adherence to taking medication shows there is no relationship (p value 0.279). Discussion: It can be concluded that there is no relationship between knowledge and motivation and compliance with taking anti-tuberculosis medication in TB patients, as community health center nurses need to carry out health education about TB and provide motivation to TB patients using a therapeutic approach.